Walter Citrine (1887-1983) (1924)
1924 1918-1939 "Walter Citrine (1887-1983)" [T0113.jpg], 1924 Walter Citrine (1887-1983) was born in Liverpool and trained as an electrician, studying languages, book-keeping and shorthand at evening classes. In 1914, he became Mersey District Secretary of the Electrical Trades Union and in 1920, Assistant General Secretary. In 1924, he became assistant secretary of the TUC and following the death of Fred Bramley in 1925, acting General Secretary, before being elected General Secretary in 1926. He took a close interest in international trade union affairs and was President of the International Federation of Trade Unions 1928-1945. He served on many public bodies and was made a Baron on leaving the TUC in 1946. Thereafter, he served on various public boards.